Analisis Faktor Lingkungan yang Mempengaruhi Keberadaan Tikus Positif Bakteri Leptospira sp. di Kota Kendari - Andi Arahmadani Arasy; Nurjazuli; M. Sakundarno Adi (Postgraduate, University of Mataram, 2023)
Rats have the potential to transmit Leptospirosis to humans. The incidence of leptospirosis in Sulawesi Province in 2017 there were 2 suspected cases of leptospirosis in Silea Village, Buke District, Kab. South Konawe, which is directly adjacent to the city of Kendari, and the leptospirosis suspect finally died. In 2022, suspected cases of leptospirosis will increase again to 4 cases, this data is based on laboratory examinations which show positive leptospirosis in Kendari City. The aim of the research is to determine environmental factors that influence the presence of mice, including the presence of rubbish, temperature, air humidity, standing water, sewer conditions and identification of Leptospira sp bacteria in caught mice. The design of this research is cross sectional. Collecting the results of observations and examination of leptospira bacteria in rat kidneys was carried out using Portable PCR, while determining the type of leptospira serotype was carried out using the MAT (Microscopic Agglutination Test). The results of this study found that the variable temperature (Ï = 0.014), the variable humidity (Ï = 0.035), the variable the presence of rubbish and the condition of the sewers (Ï = 0.000) which can be interpreted as that there is a relationship between several environmental factors and the presence of mice positive for Leptospira sp bacteria. . Meanwhile, for the waterlogging variable (Ï = 0.281), it was concluded that there was no relationship between waterlogging and the presence of mice and positive Leptospira sp bacteria. There is a relationship between temperature, humidity, the presence of rubbish, and the condition of the sewers and the presence of mice positive for leptospira sp bacteria. in Kendari City in 2023. People in Kendari City should pay more attention to the cleanliness of their living environment.